1999
DOI: 10.1038/sj.bmt.1701543
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal amphotericin (AmBisome) in the prophylaxis of fungal infections in neutropenic patients: a randomised, double-blind, placebo-controlled study

Abstract: Summary:Liposomal amphotericin (AmBisome) 2 mg/kg three times weekly was compared with placebo as prophylaxis against fungal infection in patients undergoing chemotherapy or bone marrow transplantation (BMT) for haematological malignancies. Prophylaxis began on day 1 of chemotherapy and continued until neutrophils regenerated or infection was suspected. Of 161 evaluable patients, 74 received AmBisome and 87 received placebo. Proven fungal infections developed in no patients on AmBisome and in three on placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(84 citation statements)
references
References 21 publications
1
82
0
1
Order By: Relevance
“…[78][79][80] A second placebo-controlled but underpowered trial also failed to disclose an advantage of liposomal amphotericin B 2 mg/kg/tiw. 81 Recently a randomized clinical trial (n= 132) compared liposomal amphotericin B 50 mg q48h with no prophylaxis in a population with hematologic malignancies. In this reasonably sized and dosed study on the prophylactic properties of the drug the investigators observed a significant reduction in the rates for proven and probable invasive fungal infections as well as IFI-attributable mortality rates.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…[78][79][80] A second placebo-controlled but underpowered trial also failed to disclose an advantage of liposomal amphotericin B 2 mg/kg/tiw. 81 Recently a randomized clinical trial (n= 132) compared liposomal amphotericin B 50 mg q48h with no prophylaxis in a population with hematologic malignancies. In this reasonably sized and dosed study on the prophylactic properties of the drug the investigators observed a significant reduction in the rates for proven and probable invasive fungal infections as well as IFI-attributable mortality rates.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…82 The results contrast those of a previous placebo controlled trial evaluating a similar approach. 81 A pilot trial evaluated a novel loading dose concept of liposomal amphotericin B 10 mg/kg qw; while the regimen was feasible in acute leukemia, it was associated with adverse events leading to treatment discontinuation in 6 of 8 stem cell recipients. 83 Intravenous Amphotericin B Lipid Complex and Amphotericin B Colloidal Dispersion prophylaxis may be conceivable as well.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…6,8 -10,12,15-17 Although amphotericin B prophylaxis has not been evaluated critically evaluated in patients with hematologic malignancies, its efficacy as a prophylactic antifungal agent has been well documented in patients undergoing HSCT-another patient population at high risk for developing fungal infections. 2,18,[25][26][27] The results of 4 randomized, double-blind, placebocontrolled clinical trials comparing low-dose amphotericin B (0.1 mg/kg per day) with L-AmB (1 mg/kg per day or 2 mg/kg 3 times weekly) as antifungal prophylaxis in patients undergoing HSCT showed that both drugs are effective in preventing documented or suspected fungal infections (low-dose amphotericin B, 21-53%; L-AmB, 36 -83%) 18,[25][26][27] ; these infection rates are comparable to the infection rates observed in our study. The rates of documented fungal infections in our historical control study are slightly higher than the rates observed in prospective, controlled clinical trials evaluating low-dose amphotericin B and L-AmB in patients undergoing HSCT (0 -2% vs. 0 -3%, respectively).…”
mentioning
confidence: 99%
“…The studies supporting these practices do not always reach a definitive conclusion in terms of modification of existing clinical practice. [1][2][3][4][5][6][7][8][9][10][11][12][13] Therefore, guidelines have been formulated for the prevention of infections following HSCT, 14,15 and have been endorsed by the Centers for Disease Control and Prevention, Infectious Diseases Society of America, and American Society for Blood and Marrow Transplantation. These evidence-based reviews have made weighted recommendations for the use of antimicrobial agents as prophylaxis for bacterial, viral, and fungal pathogens.…”
mentioning
confidence: 99%